Integrating Multiple Techniques to Estimate Population Size of an Impacted Dusky Dolphin’s Population in Patagonia, Argentina - Degrati, Mariana; Loizaga, Rocio; Coscarella, Mariano A.; Sueyro, Nicolás; Crespo, Enrique A.; Dans, Silvana L. (Frontiers in Marine Science, 2020)
Successful conservation strategies require an accurate estimation of population size and this parameter is one of the most important factors that determine the rate of various evolutionary processes. In this study we integrated information from genetic, photo-identification and aerial surveys of dusky dolphins to determine the effective population size and the number of dolphins that inhabit the gulfs of Peninsula Valdés (GN and GSJ) and are exposed to tourism vessel traffic. Photo-identification sessions and biopsies samples were collected from a research vessel between 2004 and 2013 to estimate the number of dolphins in the area by capture-recapture methods and the effective population size using mtDNA data. In addition, 4 aerial surveys were carried out using line transects to estimate density via distance sampling. The long-term effective size estimated was 992.87-1103.19 individuals. During the photo-identification period and applying a mark rate of 0.416 the total estimated individuals in GN was 374 (95% CI:237-511). For GSJ the estimated individuals in the area was 55 (95% CI: 2-108, mark rate 0.692). From aerial surveys, the overall density estimate was D ̂=0.13 dolphins/km2 (95% CI: 0.052 - 0.35; CV:49.60). The estimation for GN was 325 (95% CI:130-875), while for GSJ, was 104 (95% CI:42-280) individuals. These are the first estimations of the number and the effective population size for dusky dolphins in a small-scale area along north Patagonia. Dusky dolphins groups are impacted by anthropogenic activities, therefore the information reported here contributes population information to help to the species management and conservation.